Patient perspectives on recall period and response options in patient‐reported outcome measures for chronic rhinosinusitis symptomatology: A pilot study. (21st April 2021) - Gengler, Isabelle; Kavoosi, Tazheh A.; McCann, Adam C.; Trope, Michal; Lindsey, Brentley A.; Speth, Marlene M.; Sassler, Alfred M.; Seiden, Allen M.; Phillips, Katie M.; Sedaghat, Ahmad R.
Abstract: Objective: Patient‐reported outcome measures (PROMs) for assessment of chronic rhinosinusitis (CRS) employ a variety of recall periods and response scales for reporting CRS symptom burden. CRS patient perspective is unknown with respect to recall periods and response scales in PROMs. Design: Cross‐sectional study. Setting: Tertiary rhinology clinic. Participants: Sixty three adults with CRS. Main outcome measures: Participants were asked to choose which CRS symptom recall period—1 day, 2 weeks, 1 month or greater than 1 month—was most reflective of their current disease state and best to base treatment recommendations (including surgery) upon. Participants were also asked to report which of six response scales (one visual analogue scale [VAS] and five Likert scales ranging from four to eight items) were easiest to use and understand, and most preferred. Results: A majority of participants felt the current state of their CRS symptoms was best reflected by a recall period of 2 weeks to 1 month; however, patients preferred that recommendations about treatments, including endoscopic sinus surgery, be determined by symptoms experienced over at least a one‐month period. Participants generally found the VAS and seven‐item Likert scale to be the easiest to use and understand, and their most preferred scales. No patient characteristics associated with preferences for recall periods or response scales. Conclusion: Future PROMs for CRS symptoms should consider assessment of symptoms over a one‐month time frame and use either a VAS or seven‐item Likert response scale to optimally balance reflection of current disease state, need for intervention and patient preference.